(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper focuses on the life and historical narrative, spiritual message, and socio-religious impact of Hazrat Khwaja Muin-ud-Din Chishti (1141–1236), highlighting his role in shaping Sufi thought and practice in the Indian Subcontinent through the Chishtia Order. Adopting a qualitative historical approach, this study examines how Khwaja Muin-ud-Din Chishti’s teachings, missionary activities, and ethical worldview influenced the masses, particularly during spiritual gatherings, khānqāh-centered practices, and public interactions with diverse communities. His emphasis on love, tolerance, service to humanity, and peaceful coexistence created a lasting spiritual environment that appealed equally to Hindu and Muslim populations. The paper underscores how his inclusive Sufi methodology contributed to the diffusion of Islamic values without coercion, fostering social harmony and moral reform in a pluralistic society. As the founder of the Chishtia Order in the Subcontinent, Khwaja Muin-ud-Din Chishti laid the intellectual and spiritual foundations upon which later Chishti Sufis, including Amir Khusrau, built their cultural and literary expressions. The central question addressed in this research is, how did the life, work, and spiritual legacy of Khwaja Muin-ud-Din Chishti shape the Chishtia tradition and emerge as a defining force in the religious and cultural history of medieval India?